2010
DOI: 10.1002/adsc.201000128
|View full text |Cite
|
Sign up to set email alerts
|

Chirally Modified Platinum Nanoparticles Stabilized by Dendritic Core‐Multishell Architectures for the Asymmetric Hydrogenation of Ethyl Pyruvate

Abstract: In this paper we present the asymmetric hydrogenation of a-keto esters with platinum nanoparticles homogeneously stabilized in dendritic coremultishell architectures. The main focus lies on recycling and metal leaching, because little is reported so far about these aspects. It is shown that the stabilizing polymer allows for the efficient modification of the Pt surface with the chiral alkaloid cinchonidine, thereby inducing enantioselectivity and enhancing the reaction rate in the asymmetric hydrogenation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…As the authors pointed out, this approach opens a new avenue to endow the chirality to metal nanoparticles, which might have a promising application as chiral catalysts for asymmetric synthesis. In relation to this work, Haag and coworkers have reported that Pt DSNs allows the modification of Pt NP surface with a small chiral agent, and then can be used to catalyze hydrogenation with a relative high enantiometric excess (ee) value [37].…”
Section: Figurementioning
confidence: 98%
“…As the authors pointed out, this approach opens a new avenue to endow the chirality to metal nanoparticles, which might have a promising application as chiral catalysts for asymmetric synthesis. In relation to this work, Haag and coworkers have reported that Pt DSNs allows the modification of Pt NP surface with a small chiral agent, and then can be used to catalyze hydrogenation with a relative high enantiometric excess (ee) value [37].…”
Section: Figurementioning
confidence: 98%
“…Then, using a controlled etching technique (by treating the sample with strong base at elevated temperature), allowed formation of a thin shell surrounding the Au-NP core. 250 Mainly comprising ''organic'' materials, special types of coremultishell NPs have been introduced recently involving supramolecular dendritic assemblies, which have potential applications in drug/dye/metal ions delivery 251-257 as well as catalysis [258][259][260] etc. 12).…”
Section: Synthesis Of Core-shell Nanocatalystsmentioning
confidence: 99%
“…12). [258][259][260] 3.1.1.3.3. 244 The particle-size (and also shell thickness) was shown to be easily controllable and in good agreement with calculated values.…”
Section: Synthesis Of Core-shell Nanocatalystsmentioning
confidence: 99%
“…The evaluation of the catalytic activity of DENs catalysts are generally from the selectivity, activity (such as the turnover frequency, TOF the number of revolutions of the catalytic cycle per unit time, typically sec, min, or hrs), and stability. DENs catalysts have been shown to be able to considerably enhance the stability 82,83 and selectivity 84 of the metal catalyst. In addition, Bronstein and Shifrina reported that catalytically active metal nanoparticles are formed in a void in its host dendrimer and their surface could not be completely covered by the ligands, which thus provides a unique access for the reactant molecules to be adsorbed on the surface thereby facilitating the catalytic reaction.2…”
Section: Applications Of Bimetallic Dens In Catalysismentioning
confidence: 99%